Point-of-care ultrasound for monitoring catheter tip location during umbilical vein catheterization in neonates: a prospective study - Xie, Hao-Qiang; Xie, Cai-Xuan; Liao, Jin-Feng; Xu, Feng-Dan; Du, Bang; Zhong, Bai-Mao; He, Xiao-Guang; Li, Ning (Frontiers in Pediatrics, 2023)
Background Point-of-care ultrasound (POCUS) can be used to guide umbilical vein catheter placement in real time and monitor catheter tip position, allowing avoidance of serious complications due to catheter malposition.This study aims to explore the effectiveness of POCUS in guiding venous catheter insertion and monitoring complications. Methods Sixty-eight neonates with ultrasound-guided venous catheter insertion at the Neonatal Department of Dongguan Children’s Hospital between December 2020 to February 2022 were included. POCUS was applied to monitor catheter tip location daily until catheter removal. A displacement range exceeding the intersection of the inferior vena cava and right atrium by ±0.5 cm was considered misalignment. Results Sixty-four cases had a displaced catheter tip (94.1%, 64/68), with a median displacement distance of 0.4 cm (minimum −0.2 cm, maximum 1.2 cm). There were 10 neonates with a misalignment (14.7%, 10/68) caused by displacement.Displacement usually occurs within 2-4 days after placement, with displacement rates of 94.1% (64/68), 90.6% (58/64), and 98.3% (59/60) on days 2, 3, and 4, respectively, and was still displaced on post-placement day 9. In addition, misalignment mainly occurs on the second day after placement. During the monitoring process, 58 neonates had catheter tip displacement ≥ 2 times, resulting in 252 displacement incidents and 22 misalignment incidents. Among them, the catheter tip migrated outwards from the inferior vena cava for 7 times, all of which were removed in time. Ultrasound was used for positioning 486 times, and X-ray was indirectly avoided 486 times. Conclusion The catheter tip is prone to displacement and misalignment after umbilical vein catheterization, which most commonly occurs on days 2–4. POCUS is recommended for daily monitoring of the tip location during umbilical vein catheterization, until catheter removal.